A New Species of Dendrobium Sw. (Orchidaceae) from Meghalaya, India - Deori, Chaya; Sarma, S. K.; Hynniewta, T. M.; Phukan, S. J. (Rheedea, 2006)
A new species, Dendrobium meghalayense C. Deori et al., is described and illustrated from Khasi and Jaintia Hills district, Meghalaya. It differs from its allied species D. longicornu Lindi. and D. wattii (Hook. f.) Reichb. f. in having an unlobed rhomboid lip, emarginate-mucronate and dentate-serrate at apex, leaf apices obtusely bilobed and petal margins subserrate towards apex.